(3-5i)-(-7+2i)=

Simple and best practice solution for (3-5i)-(-7+2i)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3-5i)-(-7+2i)= equation:


Simplifying
(3 + -5i) + -1(-7 + 2i) = 0

Remove parenthesis around (3 + -5i)
3 + -5i + -1(-7 + 2i) = 0
3 + -5i + (-7 * -1 + 2i * -1) = 0
3 + -5i + (7 + -2i) = 0

Reorder the terms:
3 + 7 + -5i + -2i = 0

Combine like terms: 3 + 7 = 10
10 + -5i + -2i = 0

Combine like terms: -5i + -2i = -7i
10 + -7i = 0

Solving
10 + -7i = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + -7i = 0 + -10

Combine like terms: 10 + -10 = 0
0 + -7i = 0 + -10
-7i = 0 + -10

Combine like terms: 0 + -10 = -10
-7i = -10

Divide each side by '-7'.
i = 1.428571429

Simplifying
i = 1.428571429

See similar equations:

| 8k-6*3-2k= | | 4*6t+9-10t= | | 48-x=4*x/7 | | 1/3p=-2 | | 5/2x+3=13 | | 4(x+3y)-24=0 | | (R/s)=(t/(s+t)) | | x^2+-3= | | 3(6k-4.5)=-21.5-5.5k | | -8y+9x-4=0 | | 3m+2*5m-7= | | 5(4/5) | | x^2=2x+20 | | 3n^2-n+4=0 | | -8y+7-4.5y=-27.5 | | (5+2x)*x=403 | | 11a^2-4a-13=0 | | -5+5*x+4= | | 1/5(x-1)=12 | | x/8+6=74 | | 18(x+2)/9x+5 | | (37b-5)-9(4b+1)=-3 | | 5x-7=2x^2+3(3) | | 3.5x+6.5+7=-20.5 | | 18(x+2)=9x+5 | | (47+x)/3=11+x | | -6x^4y^3z-12x^5y^3-18x^4y^2z=0 | | -6x-8=3x+10 | | 5y+2(y-4)=5(y+1)-4 | | 5(2-x)+8=3(x-6) | | (5x-7)=(4x+11)(x) | | 48-x=4*a/7 |

Equations solver categories